Unbundling Faculty Roles in Online Distance Education Programs - Tucker, Jan P.; Neely, Patricia W. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
Many colleges and universities are expanding their current online offerings and creating new programs to address growing enrollment. Institutions often utilize online education as a method to serve more students while lowering instructional costs. While online education may be more cost effective in some situations, college decision makers need to consider the full range of cost implications associated with these online offerings. The unbundling of faculty roles in online distance education programs is one cost consideration that is often overlooked. As the faculty role has become more distributed, so have the costs associated with providing instruction and instructional support. This paper reviews the hidden costs associated with the unbundling of the faculty role and presents a framework for calculating the true costs of the unbundled faculty role.